NIAT PEDAGANG PASAR DALAM MENGGUNAKAN SISTEM E-RETRIBUSI PASAR (Fakultas Ekonomi Universitas Wisnuwardhana, 2022)
Theory of Planned Behavior is a theory that underlies planned human behavior in the use of technology. In order to increase the results of Regional Original Revenue and PAD Transparency, the government needs to innovate to increase people's intentions in fulfilling levy responsibilities. This study aims to test and provide empirical evidence related to Market Traders' Intentions in the Use of the E-Retribution Market system. This study uses a survey method conducted on market traders in the city of Malang. The data obtained in this research is processed with the help of the Smart PLS2.0 analysis tool. The test results show that perceived usefulness, perceived convenience, and perception of fun affect the attitude of using Market E-retribution. Attitudes, Social Factors, Facility Conditions affect the Intention to Use Market E-retribution. Self-Confidence has been proven that it has no effect on the Intention to Use Market E-retribution. The results of this study are expected to be able to contribute to the government in developing the Regional Original Revenue policy. The results of this study are also expected to provide a wealth of varied findings in the Theory of Planned Behavior.Keywords: Market E-retribution, Intention, Attitude